2014
DOI: 10.1167/tvst.3.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Nonthermal Dielectric Barrier Discharge (DBD) Plasma Suppresses Herpes Simplex Virus Type 1 (HSV-1) Replication in Corneal Epithelium

Abstract: Nonthermal plasma is a versatile tool that holds great biomedical potential for ophthalmology, where it is being investigated for wound healing and sterilization and is already in use for ocular microsurgery. The anti-HSV-1 activity of DBD plasma demonstrated here could be directly translated to the clinic for use against drug-resistant herpes keratitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
35
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 41 publications
3
35
0
2
Order By: Relevance
“…The increase in virucidal effect with increasing plasma exposure time is probably due to an increase in the production of reactive species in solution, as is illustrated by the reduction of the pH with increasing treatment time. This is in agreement with the results of Alekseev et al (23), who found that reduction in the infectivity of herpes simplex virus 1 was proportional to the exposure time when the infection medium was treated with nonthermal DBD air-based plasma. A similar effect was found with this plasma source in treating Pseudomonas aeruginosa (24).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The increase in virucidal effect with increasing plasma exposure time is probably due to an increase in the production of reactive species in solution, as is illustrated by the reduction of the pH with increasing treatment time. This is in agreement with the results of Alekseev et al (23), who found that reduction in the infectivity of herpes simplex virus 1 was proportional to the exposure time when the infection medium was treated with nonthermal DBD air-based plasma. A similar effect was found with this plasma source in treating Pseudomonas aeruginosa (24).…”
Section: Discussionsupporting
confidence: 93%
“…Since previous studies reported that the biological activity of CGP is multifactorial and highly dependent on plasma type and exposure parameters (6,23,40), we studied the effects of several operational and exposure parameters affecting the reactivity of the resultant cold plasma and its virucidal activity in order to reach the objective of complete inactivation of FCV in solution. The effects of the plasma generation power, feed gas mixtures, exposure time, exposure distance, and virus suspension medium were studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CAP has a complex chemical composition and some of the charged particles detected in the CAP, such as NO - , NO 2 - , OH - , O - , as well as reactive oxygen species (O 3, O), have important biological and biomedical activities. The ongoing research suggests that CAP can be used for decontamination and sterilization, and appears to be quite effective in virus inactivation [14]. The mechanisms behind the anti-viral activity of CAP are poorly understood, but may include both a direct effect on viral particles via bioactive ions and indirect suppression via modification of cell surface receptors important for viral replication [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, the plasma produced at the higher pulse rate also generates greater/cytotoxic concentrations of ROS and RNS (Liu et al, 2014;Zhang et al, 2014). To date, there has been a lack of studies characterizing each plasma type and condition, which has led to a disconnect in determining how the different plasmas affect biological tissues and cellular processes (Jiang et al, 2009;Duval et al, 2013;Alekseev et al, 2014;Li et al, 2014). To further confound our understanding, isolated cells treated with plasma also tend to react much differently than treated tissues (unpublished data).…”
Section: Introductionmentioning
confidence: 99%